Neuropeptide Y in the Adult and Fetal Human Pineal Gland - Møller, Morten (Hindawi Publishing Corporation, 2014)
Neuropeptide Y was isolated from the porcine brain in 1982 and shown to be colocalized with noradrenaline in sympathetic nerve terminals. The peptide has been demonstrated to be present in sympathetic nerve fibers innervating the pineal gland in many mammalian species. In this investigation, we show by use of immunohistochemistry that neuropeptide Y is present in nerve fibers of the adult human pineal gland. The fibers are classical neuropeptidergic fibers endowed with large boutons en passage and primarily located in a perifollicular position with some fibers entering the pineal parenchyma inside the follicle. The distance from the immunoreactive terminals to the pinealocytes indicates a modulatory function of neuropeptide Y for pineal physiology. Some of the immunoreactive fibers might originate from neurons located in the brain and be a part of the central innervation of the pineal gland. In a series of human fetuses, neuropeptide Y-containing nerve fibers was present and could be detected as early as in the pineal of four- to five-month-old fetuses. This early innervation of the human pineal is different from most rodents, where the innervation starts postnatally.